Epidemiological changes in infectious diseases during the coronavirus disease 2019 pandemic in Korea: a systematic review - Jong Gyun Ahn (The Korean Pediatric Society, 2022)
In the era of the coronavirus disease 2019 (COVID-19) pandemic, countries worldwide have implemented several nonpharmaceutical interventions (NPIs) to contain its spread before vaccines and treatments were developed. NPIs included social distancing, mask wearing, intensive contact tracing and isolation, and sanitization. In addition to their effectiveness at preventing the rapid spread of COVID-19, NPIs have caused secondary changes in the epidemiology of other infectious diseases. In Korea, various NPI stages have been implemented since the first confirmed case of COVID-19 on January 20, 2020. This review, based on a PubMed database search, shows the impact of NPIs on several infectious diseases other than severe acute respiratory syndrome coronavirus 2 in the COVID-19 pandemic era in Korea.